Analysis of factors influencing the development of paravertebral ossification in the distant future after artificial disc replacement for cervical disc herniation - Xu, Bohan; Zhao, Huiying; Tian, Xin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
To investigate and analyze the factors that contribute to the occurrence of disc ossification in patients in the distant future when artificial disc replacement surgery is applied in the treatment of patients with cervical disc herniation, to explore the clinical characteristics and to provide a research basis for subsequent treatment work. METHODS: This study was conducted from September 2021 to June 2022, and a total of 504 patients with cervical disc herniation admitted by the medical staff in our hospital during this period were used as study subjects. After admission, all patients were treated with artificial disc replacement surgery and were followed up by the medical staff for one year after completion of treatment. Patients were divided into a control group (n=252) who recovered well without disc ossification and an experimental group (n=252) who developed disc ossification after treatment. The medical staff analyzed the individual conditions of the two groups to determine the differences between the groups and to analyze the risk factors for the development of disc ossification in the patients. RESULTS: The patients' imaging results were evaluated, and significant differences were found between the experimental group of patients and the control group (p < 0.05). CONCLUSION: Patients with cervical disc herniation are at risk of distant disc ossification after artificial disc replacement surgery. To improve the clinical efficacy of the patients, the treatment plan needs to be adjusted according to the individual conditions of the patients, thereby safeguarding the efficacy of the patients.